2005
DOI: 10.1002/cbf.1189
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sialidase from bloodstream forms ofTrypanosoma vivax

Abstract: Sialidase (EC: 3.2.1.18) from Trypanosoma vivax (Agari Strain) was isolated from bloodstream forms of the parasite and purified to apparent electrophoretic homogeneity. The enzyme was purified 77-fold with a yield of 32% and co-eluted as a 66-kDa protein from a Sephadex G 110 column. The T. vivax sialidase was optimally active at 37 degrees C with an activation energy (E(a)) of 26.2 kJ mole(-1). The pH activity profile was broad with optimal activity at 6.5. The enzyme was activated by dithiothreitol and stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Although the experimental demonstration of sialidase activity in T. congolense bloodstream forms was quite recent (116), a direct interaction of this trypanosome with RBC resulting in alteration of these cells had already been shown in earlier studies (13,14). T. vivax sialidase was shown to present some host specificity, desialating camel, goat, and zebu RBC, while those from mice, dogs, and NЈDama bulls were shown to be resistant (26). In T. evansi, an isolated sialidase was found to desialate ghost RBC in the following order of efficiency: mouse, rat, camel, goat, and dog (115).…”
Section: New Candidatesmentioning
confidence: 94%
See 2 more Smart Citations
“…Although the experimental demonstration of sialidase activity in T. congolense bloodstream forms was quite recent (116), a direct interaction of this trypanosome with RBC resulting in alteration of these cells had already been shown in earlier studies (13,14). T. vivax sialidase was shown to present some host specificity, desialating camel, goat, and zebu RBC, while those from mice, dogs, and NЈDama bulls were shown to be resistant (26). In T. evansi, an isolated sialidase was found to desialate ghost RBC in the following order of efficiency: mouse, rat, camel, goat, and dog (115).…”
Section: New Candidatesmentioning
confidence: 94%
“…RBC surface alterations have indeed been shown to be caused by bloodstream T. vivax, T. congolense, and T. evansi sialidases, thus leading to their subsequent phagocytosis (26,40,115,116). Although the experimental demonstration of sialidase activity in T. congolense bloodstream forms was quite recent (116), a direct interaction of this trypanosome with RBC resulting in alteration of these cells had already been shown in earlier studies (13,14).…”
Section: New Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other cases, trypanosomal (trans-) sialidases are produced in the so-called 'bloodstream form' (i.e. the mammalian host stage) and their actions are thought to be directly correlated with the induced pathology in the infected mammalian host (Schenkman et al, 1991;Nok & Balogun, 2003;Buratai et al, 2006). In T. cruzi, the only intracellular trypanosome, it has been shown that its transsialidases play a role in host-cell invasion, parasite virulence and immune suppression (Schenkman et al, 1992;Buschiazzo et al, 2002;Jacobs et al, 2010;Giorgi & de Lederkremer, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In T. cruzi, the only intracellular trypanosome, it has been shown that its transsialidases play a role in host-cell invasion, parasite virulence and immune suppression (Schenkman et al, 1992;Buschiazzo et al, 2002;Jacobs et al, 2010;Giorgi & de Lederkremer, 2011). In T. vivax infections, trans-sialidase activity has been proposed to be linked to the typically observed severe anaemia (Bratosin et al, 1998;Buratai et al, 2006;Guegan et al, 2013). Hence, for disease-associated trypanosomal transsialidases, unravelling their structure-function relationship might yield insights into the molecular mechanisms behind the onset of trypanosomosis-induced pathologies.…”
Section: Introductionmentioning
confidence: 99%